Informal m-health: How are young people using mobile phones to bridge healthcare gaps in Sub-Saharan Africa?. (October 2015) - Hampshire, Kate; Porter, Gina; Owusu, Samuel Asiedu; Mariwah, Simon; Abane, Albert; Robson, Elsbeth; Munthali, Alister; DeLannoy, Ariane; Bango, Andisiwe; Gunguluza, Nwabisa; Milner, James
Abstract: The African communications 'revolution' has generated optimism that mobile phones might help overcome infrastructural barriers to healthcare provision in resource-poor contexts. However, while formal m-health programmes remain limited in coverage and scope, young people are using mobile phones creatively and strategically in an attempt to secure effective healthcare. Drawing on qualitative and quantitative data collected in 2012–2014 from over 4500 young people (aged 8–25 y) in Ghana, Malawi and South Africa, this paper documents these practices and the new therapeutic opportunities they create, alongside the constraints, contingencies and risks. We argue that young people are endeavouring to lay claim to a digitally-mediated form of therapeutic citizenship, but that a lack of appropriate resources, social networks and skills ('digital capital'), combined with ongoing shortcomings in healthcare delivery, can compromise their ability to do this effectively. The paper concludes by offering tentative suggestions for remedying this situation. Highlights: Investigates how young people in Africa use mobile phones to seek healthcare. Compares practices across rural and urban sites in Ghana, Malawi and South Africa. Mobile phones can help bridge healthcare gaps but do not erase inequalities. Lack of access to 'digital capital' constrains 'informal m-health' for the rural poor. Facilitating safe 'informal m-health' for young people should be a policy priority.